Antibiotics Utilization Pattern in Pediatrics in a Tertiary Care Teaching Hospital - Prabahar, Dr. Kousalya (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: Children have high rates of minor infection, and because of their increased susceptibility to serious bacterial infection, they are frequently prescribed with antibiotics. The main aim of the study was to evaluate the antibiotics utilization pattern and check the adherence to the antibiotic policy in pediatric patients of a tertiary care teaching hospital. Materials and Methods: This prospective observational study was conducted for a period of 6 months in the inpatient Department of Pediatrics of a tertiary care teaching hospital after getting approval from the Research and Ethics Committee. 90 children from 1 month to 18 years age of either sex admitted to pediatric ward prescribed with antibiotics were included for the study, after getting informed consent from their parents. The lab data were noted down on follow-up. The patient charts were followed up throughout the period of hospitalization for drug interactions. The antibiotic utilization pattern was studied from the revised antibiotic prescribing policy of the Department of Pediatrics. The drug interactions were found using drugs.com. Results: Cephalosporins was the common class of antibiotics prescribed and majority of antibiotics were prescribed for a period of 1-5 days. There was 83.33% complete adherence to the prescribed medication, no significant drug interactions were found in this study. Discussion and Conclusion: Pharmacist plays a major role in monitoring, adherence of drug according to the guidelines, and drug interactions. This study helps to promote appropriate antibiotic usage and serve as a check mark to the health-care professionals.